THE EFFECT OF COMMUNICATION, WORK DISCIPLINE, AND MOTIVATION ON EMPLOYEE JOB SATISFACTION AT PT. JAYA ANUGRAH SUKSES ABADI MEDAN (CASE STUDY AT BRASTAGI SUPERMARKET, CAMBRIDGE BRANCH) - Widya Sari; Micheal Chandra; Nadia Tamara; Junianti Theodora; Tahnia -; Kevin - (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
PT. Jaya Anugrah Sukses Abadi Medan is a retail company, which sells community staples andother equipment. This company has been around for 14 years. Problems in PT. Jaya AnugrahSukses Abadi Medan lies in employee job satisfaction, where some employees feel less satisfiedcarrying out tasks in the company related to Communication, Work Discipline, and Motivation.Theories used to support this study were related to Human Resource Management closely related toCommunication, Work Discipline, Motivation, and Job Satisfaction. Quantitative descriptiveresearch type was employed as the research method of this study. The nature of this study wasdescriptive explanatory. The data collection technique carried out by using questionnaires,interviews, and documentation studies. The obtained data were then analyzed using multiple linearregressions. From the research population of 103 company employees with 30 people were chosenfor the validity test. The analysis found tcount values on the communication of 2.831, work disciplineof 2.962, motivation of 2.059, and Fcount of 6.816. The results indicate that the coefficient ofdetermination was 14.6%. It can be concluded that simultaneously and partially communication,work discipline, and motivation had a significant and positive influence on job satisfaction at PT.Jaya Anugrah Sukses Abadi Medan